Dynamic spectrum access mechanism based on graphical evolutionary game in radio networks - Fang-wei LI; Ying-hui YUAN; Jiang ZHU (Tongxin xuebao)
In order to realize efficient data transmission for users in radio networks,a dynamic spectrum access mechanism based on graphical evolutionary game was proposed for the bounded rationality characteristic of users,while graphical game can better reflect the actual game relationship among users.Meanwhile,a dynamic spectrum access algorithm and corresponding dynamic equation were designed for the mechanism to reduce the complexity of the game,and could converge to Nash equilibrium with faster speed and obtain higher system throughput and utility.Theoretical analysis showed that the dynamic equation was globally asymptotically stable,which illustrated that when user deviated because of bounded rationality and it was still able to guarantee faster converge and fewer performance deviation.Simulation comparison verifies the superiority above.